Morphosyntax aspects of ditransitive constructions with the verb DAR ‘to give’ in Portuguese Sign Language - Celda Choupina (Linguística : Revista de Estudos Linguísticos da Universidade do Porto, 2016)
In this study we analyze some morphosyntactic aspects of the verb DAR ‘to give’ in LGP (Portuguese Sign Language) in simple declarative sentences, in particular, two properties: (i) the position of the arguments regarding the verb and (ii) the agreement of the verb with the internal arguments. We defend that the basic word order in ditransitive constructions is S V DO IO, although other syntactic processes, such as simple and double topicalization may, apparently, call into question the existence of that basic pattern.